Mixed convective eyring-powell ferro magnetic nanofluid flow suspension towards a stretching surface with buoyancy effects through numerical analysis - Duraihem, Faisal Z.; Sher Akbar, Noreen; Saleem, Salman (Frontiers in Materials, 2023)
This article examines the impact of buoyancy on the magnetic Eyring-Powell nanofluid flow toward a stretching surface. Coupled similarity equations are created from the governing flow equations. For the particular instance of pure fluid flow, the numerically computed self-similar results are matched with the available literature and found to be in acceptable harmony. The shooting approach was used to arrive at numerical computations to the constitutive ordinary differential equations. The impacts of different fluid flow parameters, nano concentration parameters and heat transfer, are shown graphically for both aiding and opposing flows. It has been discovered that for both aiding and opposing problems, the skin friction is less affected by the buoyant force brought on by temperature differences. Under buoyancy, the rate of heat transfer increments for aiding flow problem while it declines for opposing flow.